Morocco : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper assesses financial sector vulnerabilities, the policy oversight framework, bank resolution, and financial safety nets. The assessment is intended to help Moroccan government identify key sources of systemic risk in the financial sector and implement policies to enhance its resilience to shocks and contagion. Since the 2007 Financial Sector Assessment Program update, Morocco's financial system has grown in size and complexity, with increased links between the banking and insurance sectors and a significant expansion into sub-Saharan Africa. Although banks are adequately capitalized and profitable, with stable funding, they are vulnerable to large corporate defaults and deposit withdrawals. But the new banking law has helped in strengthening the banking sector.